Sampling across large-scale geological gradients to study geosphere–biosphere interactions - Giovannelli, Donato; Barry, Peter H.; de Moor, J. Maarten; Jessen, Gerdhard L.; Schrenk, Matthew O.; Lloyd, Karen G. (Frontiers in Microbiology, 2022)
Despite being one of the largest microbial ecosystems on Earth, many basic open questions remain about how life exists and thrives in the deep subsurface biosphere. Much of this ambiguity is due to the fact that it is exceedingly difficult and often prohibitively expensive to directly sample the deep subsurface, requiring elaborate drilling programs or access to deep mines. We propose a sampling approach which involves collection of a large suite of geological, geochemical, and biological data from numerous deeply-sourced seeps—including lower temperature sites—over large spatial scales. This enables research into interactions between the geosphere and the biosphere, expanding the classical local approach to regional or even planetary scales. Understanding the interplay between geology, geochemistry and biology on such scales is essential for building subsurface ecosystem models and extrapolating the ecological and biogeochemical roles of subsurface microbes beyond single site interpretations. This approach has been used successfully across the Central and South American Convergent Margins, and can be applied more broadly to other types of geological regions (i.e., rifting, intraplate volcanic, and hydrothermal settings). Working across geological spatial scales inherently encompasses broad temporal scales (e.g., millions of years of volatile cycling across a convergent margin), providing access to a framework for interpreting evolution and ecosystem functions through deep time and space. We propose that tectonic interactions are fundamental to maintaining planetary habitability through feedbacks that stabilize the ecosphere, and deep biosphere studies are fundamental to understanding geo-bio feedbacks on these processes on a global scale.